Corporate Governance Practices Among Management and Organizational Performance of Equity Bank. - Yudah Muwonge (Uganda Christian University, 2023)
The purpose of the study was to investigate the influence that corporate governance among management has on organizational performance in Equity Bank. The study was guided by the following specific objectives; effect of transparency on organizational performance; contribution of accountability on organizational performance; and effect of management competence on organizational performance at Equity Bank. The study adopted a case study design and a sample size of 30 respondents comprising staff was selected using simple random sampling. Data was collected using structured questionnaires and interviews. The data was analyzed using Microsoft excel. The major findings of the study revealed that there is a significant relationship between transparency and organizational performance and transparency was a predictor of bank performance. Likewise, a significant relationship was observed between accountability and organizational performance where accountability was seen to be a predictor of bank performance. Further still, the relationship between Management competence and organizational performance showed a significant relationship. In conclusion, transparency, accountability and management competence as dimensions of corporate governance, determine organizational performance at Equity Bank. The study recommends, therefore, that management of Equity Bank should make efforts to ensure that there is transparency, accountability and management competence so as to promote bank performance.
This is a dissertation.